(untitled) (Research, Society and Development, 2021)
The main concern in the commercialization of fresh pineapples is the rapid loss of post-harvest quality. One of the factors that most influence the deterioration of these fruits is the high amount of free water present, causing the degradation by microorganisms more quickly. A process that can be used to reduce the moisture content of these fruits is convection drying and/or osmotic dehydration, thus extending their shelf life. Thus, this work aimed to analyze the influence of the effect of temperature and osmotic treatment on water loss from pineapple slices. The process was carried out through a complete 22 factorial design, varying the drying temperature (70 and 100 °C) and the sucrose concentration in the osmotic solution (15 and 30%) to assess the water loss (g). In execution, the pineapple slices were immersed for 2 h in an osmotic solution and 3 h in dehydration in a conventional oven. Through the obtained results, it was observed that the best experimental condition was in the dehydration temperature of 100 ºC and in the sucrose concentration of 30%, obtaining a water loss of 16 g. Temperature had a greater effect on water loss than osmotic treatment. The mathematical model obtained through the experimental procedure explained 94.7% of the results obtained and could be used for predictive purposes.